Sex differences of brain oscillatory activity and quantitative sensory testing in people with chronic osteoarthritis pain: a cross-sectional study. (September 2022) - Vasquez-Avila, Karen; Pacheco-Barrios, Kevin; Simis, Marcel; Imamura, Marta; Battistella, Linamara; Fregni, Felipe
Abstract: Background: Chronic pain due to osteoarthritis is a debilitating and heterogeneous disease. Pain phenotypes are measured by electroencephalogram (EEG), cortical excitability indexed by transcranial magnetic stimulation (TMS), and quantitative sensory testing (QST). However, mixed evidence exists regarding the influence of biological sex on these parameters. We aimed to assess the differences in neurophysiological outcomes by sex, adjusted for demographics and clinical outcomes. Methods: This cross-sectional study was done at Hospital das Clínicas, University of Sao Paulo, in Brazil. We included adults aged 18 years or older with a clinical and radiological diagnosis of knee osteoarthritis and with chronic pain and clinical stability. Sex (female, male, or other) was self-reported. We performed multivariate linear models to assess the relationship between baseline neurophysiological outcomes (relative power from 64-channels resting-state EEG, single and paired-pulse TMS, and QST) as a dependent variable and sex as an independent variable. We adjusted for potential confounders, such as pain catastrophising, depression, anxiety, and pain (indexed by the Visual Analogue Scale [VAS] for pain or the Western Ontario and McMaster Universities Osteoarthritis Index [WOMAC] pain scale). We also adjusted by demographics including age and ethnicity (reported as White or non-White). Findings: Between Oct 29, 2018, and Aug 3, 2021, we included 108 participants (90 females and 18 males). For the EEG analyses, we excluded 42 participants due to unavailability or damaged recordings. The median age of participants was 69 years (IQR 58–80). We found a significant difference in the relative power of α and high α bands in the sensorimotor area by sex (female compared with males α power difference –0·13 [95% CI –0·25 to –0·01], p=0·02; high α power difference –0·06 [–0·12 to –0·002]; p=0·04). These differences between females and males remained significant after adjustment (α power difference –0·14 [–0·27 to –0·02], p=0·02; high α power difference –0·06 [–0·12 to –0·004]; p=0·03). These findings were also present in the parietal and occipital regions (females compared with males α power difference –0·15 [–0·31 to –0·001], p=0·04; high α power difference –0·17 [–0·33 to –0·01]; p=0·03) and remained significant after adjustment. Furthermore, pain pressure threshold average in both knees and in upper limbs were lower in females than in males (knees –3·77 [–4·82 to –2·71], p=0·001 and upper limbs –2·30 [–3·20 to –1·36]; p=0·009), even after adjustment. No relationship was found with frontal EEG band, conditioned pain modulation, and TMS. Interpretation: We highlight an important influence of biological sex in the neurophysiological signature of osteoarthritis with chronic pain. Females have less α oscillatory activity (an inhibitory marker) and lower pain thresholds, representing an underlying mechanism and a driver of chronic pain vulnerability. We suggest that biological sex and gender need to be included when developing and validating biomarkers for people with chronic osteoarthritis pain. Funding: Fundação de Amparo à Pesquisa do Estado de São Paulo.